Úloha Veletrhů Brno, a.s. při marketingové prezentaci firmy - Dospíšilová, Klára (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Bakalářská práce popisuje úlohu marketingu v oboru veletrhů a výstav, analyzuje a hodnotí společnost Veletrhy Brno, a.s. (konkrétněji Mezinárodní stavební veletrh). Výsledkem práce jsou návrhy, jejichž realizace povede k dalšímu rozvoji firmy a veletrhu.

The bachelor’s thesis describes the task of the marketing in the trade fair’s field and then it analyzes BVV Trade Fairs Brno Co, more precisely International building fair. The results of the work are proposals and their realization will lead to next advancement of the company and trade fairs.
The Work of BVV Trade Fairs Brno Co in Marketing Presentation of the Company
Keywords: Mezinárodní stavební veletrh; komunikační mix; marketing; veletrh; International building fair; communication mix; marketing; trade fair